BS3 GCN5L1 promotes diastolic dysfunction by inhibiting cardiac pyruvate oxidation. (6th June 2022) - Scott, Iain; Thapa, Dharendra; Bugga, Paramesha; Mushala, Bellina; Manning, Janet; Stoner, Michael; McMahon, Brenda; Zeng, Xuemei; Cantrell, Pamela; Yates, Nathan; Xie, Bingxian; Edmunds, Lia; et al.
Abstract : Introduction: Left ventricular diastolic dysfunction is a structural and functional condition that precedes the development of heart failure with preserved ejection fraction (HFpEF). The etiology of diastolic dysfunction includes alterations in fuel substrate metabolism that negatively impact cardiac bioenergetics, and may precipitate the eventual transition to heart failure. To date, the molecular mechanisms that regulate early changes in fuel metabolism leading to diastolic dysfunction remain unclear. However, recent work has suggested that changes in mitochondrial lysine acetylation may regulate this process in mouse models of HFpEF. Methods: We used a diet-induced obesity model and quantitative acetylproteomics in aged mice to examine the role played by mitochondrial lysine acetylation in the development of diastolic dysfunction. Wildtype and cardiac-specific GCN5L1 knockout mice (which are deficient in mitochondrial lysine acetylation) aged 5–7 months were placed on a low fat diet (10% fat) or high fat diet (60% fat) for 30 weeks. Echocardiography was performed after 30 weeks of diet to assess cardiac structure and function, followed by euthanasia. After rapid isolation, hearts were subject to quantitative acetylproteomics, respirometry measurements, and biochemical measurements of metabolic enzyme acetylation and activity. In addition, cell culture models of site-specific lysine acetylation were used to test the mechanism underlying bioenergetic changes in mouse hearts. Results: Cardiomyocyte-specific deletion of the mitochondrial lysine acetylation regulatory protein GCN5L1 prevented the development of diastolic dysfunction (measured as a change in E/e' ratio) in response to a high fat diet. Quantitative acetylproteomics demonstrated that enzymes in the mitochondrial fatty acid oxidation and pyruvate utilization pathways were most affected by GCN5L1-dependent acetylation. Deletion of GCN5L1 prevented hyperacetylation of the pyruvate dehydrogenase complex subunit PDHA1, which increased its enzymatic activity, and allowed increased pyruvate utilization in hearts from obese, aged mice. Using a cell culture model of variable PDHA1 acetylation status, we confirmed that site-specific acetylation of five PDHA1 lysine residues significantly reduced its enzymatic activity in cardiac cells in vitro. Conclusions: Our findings suggest that changes in mitochondrial protein lysine acetylation represent a key metabolic component of diastolic dysfunction that precedes the development of heart failure. Our work suggests that manipulation of PDHA1 acetylation levels in vivo may represent a novel target for therapeutic intervention in the treatment of diastolic dysfunction.